Genauigkeit. Zur Ausbildung einer epistemischen Tugend im, langen 19. Jahrhundert'. Issue 3 (5th September 2016) - Krajewski, Markus
Abstract: Exactitude. The Genesis of an Epistemic Virtue in the 'Long Nineteenth Century' . The article examines the genesis of exactitude as an epistemic virtue in both scholarly and scientific contexts in the 19th century, mainly in Prussia. Starting with an influential historiographic work on ancient metrology three semantic fields of accuracy, exactitude and precision are differentiated and pursued in their etymologies as well as applications. The historic situation between 1790 and 1860 is identified as the crucial period when the exactness of the exact sciences as well as the notion of accuracy in the humanities start to diverge from one another in order to develop an epistemic virtue each on its own.